Biophysical and textural attributes as selection indices for replacing the adopted cassava variety with the improved genotype to produce fufu - Awoyale, Wasiu; Maziya-Dixon, Busie; Oyedele, Hakeem; Adesokan, Michael; Alamu, Emmanuel O. (Frontiers in Sustainable Food Systems, 2023)
The use of the biophysical and textural qualities of fufu to choose the possible substitution of an adopted cassava variety (TMEB419-V1) with better genotypes from the breeding program was assessed in this study. Standard methods were used for the biophysical and textural attributes of the fufu produced from different cassava roots. The outcomes portray that the means of the biophysical attributes of the fufu flour from different cassava genotypes are swelling power (SWP) 13.59%, solubility index (SI) 3.41%, dispersibility 26.77%, bulk density (BD) 54.46%, and water absorption capacity (WAC) 149.44%, peak viscosity 693.97 RVU, trough viscosity 319.76 RVU, breakdown viscosity 374.21 RVU, final viscosity 433.84 RVU, setback viscosity 114.08 RVU, peak time 4.49 min, and pasting temperature 78.52oC, as well as moisture content of 4.92%, ash content of 0.52%, sugar content of 2.85%, starch content of 76.24%, amylose content of 31.68%, and cyanogenic potential content (CNP) of 3.03 mg HCN/kg. The sensory texture attributes depict that the cooked fufu dough was stretchable, slightly hard, sticky, and mouldable. The instrumental texture attribute of the cooked fufu dough is hardness 27.18 N/m2, adhesiveness -62.04 N/m2, mouldability 0.93, stretchability 0.89, and gumminess 25.26 N/m2. Similar functional (BD) and pasting (peak and breakdown viscosities) properties, and chemical composition (amylose content) to that of the control sample (V1 variety) was produced from the V6 genotype. However, the cooked fufu dough prepared from the V7 and V8 genotypes are comparable to that of the V1 variety in terms of the sensory (stretchability) and instrumental (mouldability) texture attributes, therefore, most of the genotypes may be suitable for producing fufu flour like the control sample (V1 variety) based on attributes preferred by the consumers.